2002
DOI: 10.1074/jbc.m204209200
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate 3-O-Sulfotransferase Isoform 5 Generates Both an Antithrombin-binding Site and an Entry Receptor for Herpes Simplex Virus, Type 1

Abstract: Heparan sulfates (HSs) 1 are highly sulfated polysaccharides, present on the surface of mammalian cells and in the extracellular matrix in large quantities. HSs play critical roles in a variety of important biological processes, including assisting viral infection, regulating blood coagulation and embryonic development, suppressing tumor growth, and controlling the eating behavior of mice by interacting with specific regulatory proteins (1-5). HS polysaccharides carry negative charges under physiological pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(188 citation statements)
references
References 41 publications
7
180
0
1
Order By: Relevance
“…Unlike HS, 11 and 12 do not contain the IdoUA2S-GlcNS motif. It is known that 3-OST-1 acts on GlcUA (or IdoUA)-GlcNS6S sequences, but not on IdoUA2S-GlcNS sequences (15,24,25). It is possible that the presence of IdoUA2S plays a role in down-regulating the level of 3-O-sulfation.…”
Section: S]paps To Afford N-[mentioning
confidence: 99%
“…Unlike HS, 11 and 12 do not contain the IdoUA2S-GlcNS motif. It is known that 3-OST-1 acts on GlcUA (or IdoUA)-GlcNS6S sequences, but not on IdoUA2S-GlcNS sequences (15,24,25). It is possible that the presence of IdoUA2S plays a role in down-regulating the level of 3-O-sulfation.…”
Section: S]paps To Afford N-[mentioning
confidence: 99%
“…NDST is present in four different isoforms, 6-OST is present in three different isoforms and 3-OST in seven. The isoforms have slightly different substrate specificities and unique tissue specific expression patterns (34)(35)(36)(37). It has been hypothesized that cells regulate expression levels of different isoforms of the biosynthetic enzyme in order to synthesize HS with defined saccharide sequences to achieve unique biological functions (38).…”
Section: Biosynthesis Of a Polysaccharide With Defined Sequencesmentioning
confidence: 99%
“…HS 3-OST is present in seven isoforms, including 3-OST-1, -2, -3A, 3B, -4, -5, and 6 (33,34,43). These enzymes catalyze the transfer of a sulfo group from the sulfo donor, 3′-phosphoadenosine-5′-phosphosulfate (PAPS), to the 3-OH position of a glucosamine unit.…”
Section: Substrate Specificities and Mechanism Of Action Of 3-ost Isomentioning
confidence: 99%
“…The enzyme was purified to homogeneity from L-cell conditioned medium (90) followed by cloning of the cDNA (91). The enzyme was designated HS3ST-1 since recent studies have revealed that HS3ST is present in at least six isoforms, HS3ST-1, -2, -3A -3B, -4, and -5 (Table 1) (92,93). The HS3STs, except for HS3ST-1, are type-II transmembrane proteins.…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 99%
“…HS3ST-1 transfers sulfate to C3-position of N -sulfoglucosamine and N -sulfoglucosamine -1 (93, 94). The HS3ST isoforms have distinct expression levels in various human tissues (Table 1) (92,93).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 99%